Lymphadenectomy improves outcome in dogs with resected Kiupel high‐grade cutaneous mast cell tumours and overtly metastatic regional lymph nodes. (22nd June 2022) - Chalfon, C.; Sabattini, S.; Finotello, R.; Faroni, E.; Guerra, D.; Pisoni, L.; Ciammaichella, L.; Vasconi, M. E.; Annoni, M.; Marconato, L.
Abstract : Introduction: Historically, the prognosis for dogs with stage II Kiupel high‐grade cutaneous mast cell tumours has been considered poor. Objectives: The aim of this study was to explore the impact of lymphadenectomy on outcome in dogs with Kiupel high‐grade cutaneous mast cell tumours and overt regional lymph node metastasis. Material and Methods: Data from dogs with completely staged Kiupel high‐grade cutaneous mast cell tumours with overt and/or certain regional lymph node metastasis undergoing excision of the primary tumours and adjuvant medical treatment were extracted. Dogs with a cytological diagnosis of regional lymph node metastasis that did not undergo lymphadenectomy were compared with dogs that underwent lymphadenectomy and had a histological diagnosis of overt lymph node metastasis. Results: Forty‐nine dogs were included, 18 did not undergo lymphadenectomy while 31 underwent lymphadenectomy. Median time to progression was significantly shorter in dogs that did not undergo lymphadenectomy (150 days, 95% confidence interval: 129 to 170) compared to the other dogs (229 days, 95% confidence interval: 191 to 266). Median survival time was also shorter in dogs that did not undergo lymphadenectomy (250 days, 95% confidence interval: 191 to 308) compared to dogs that underwent lymphadenectomy (371 days, 95% confidence interval: 311 to 430). On multivariable analysis, lack of lymphadenectomy was associated with higher risk of overall tumour progression (hazard ratio: 2.05, 95% confidence interval: 1.02 to 4.13), nodal progression (hazard ratio: 3.4, 95% confidence interval: 1.65 to 7.02) and tumour‐related death (hazard ratio 3.63, 95% confidence interval: 1.72 to 7.66), whereas tumour size was associated with higher risk of local recurrence (hazard ratio: 3.61, 95% confidence interval: 1.06 to 13). Clinical significance: Regional lymphadenectomy may improve outcome in dogs with biologically aggressive cutaneous mast cell tumours.